An Australian perspective on rewilding. Issue 4 (29th January 2019) - Sweeney, Oisín F.; Turnbull, John; Jones, Menna; Letnic, Mike; Newsome, Thomas M.; Sharp, Andy
Abstract: Rewilding is increasingly recognized as a conservation tool but is often context specific, which inhibits broad application. Rewilding in Australia seeks to enhance ecosystem function and promote self‐sustaining ecosystems. An absence of large‐bodied native herbivores means trophic rewilding in mainland Australia has focused on the restoration of functions provided by apex predators and small mammals. Because of the pervasive influence of introduced mesopredators, predator‐proof fences, and establishment of populations on predator‐free islands are common rewilding approaches. This sets Australian rewilding apart from most jurisdictions and provides globally relevant insights but presents challenges to restoring function to broader landscapes. Passive rewilding is of limited utility in arid zones. Although increasing habitat extent and quality in mesic coastal areas may work, it will likely be necessary to undertake active management. Because much of Australia's population is in urban areas, rewilding efforts must include urban areas to maximize effectiveness. Thus rewilding is not synonymous with wilderness and can occur over multiple scales. Rewilding efforts must recognize human effects on other species and benefit both nature and humans. Rewilding in Australia requires development of a shared vision and strategy and proof‐of‐concept projects to demonstrate the benefits. The repackaging of existing conservation activities as rewilding may confuse and undermine the success of rewilding programs and should be avoided. As elsewhere, rewilding in Australia should be viewed as an important conservation tool. Abstract : Article impact statement : Rewilding in Australia seeks to enhance ecosystem function and promote self‐sustaining ecosystems. Abstract : Una Perspectiva Australiana del Proceso de Resilvestrar Resumen: El proceso de resilvestrar es reconocido cada vez más como una herramienta de conservación, pero con frecuencia depende del contexto ambiental, lo que inhibe su aplicación generalizada. En Australia, el proceso de resilvestrar busca mejorar la función ambiental y promover los ecosistemas auto‐sustentables. Una ausencia de herbívoros nativos corpulentos significa que el resilvestreo trófico en la isla principal de Australia se ha enfocado en la restauración de las funciones que proporcionan los superdepredadores y los mamíferos pequeños. Debido a la influencia generalizada de los mesodepredadores introducidos, los cercos contra depredadores y el establecimiento de poblaciones en islas libres de depredadores son estrategias comunes de resilvestreo. Esto coloca al resilvestreo australiano aparte del que ocurre en muchas jurisdicciones y proporciona información relevante a nivel mundial, pero presenta retos para la restauración de la función en paisajes más amplios. El resilvestreo pasivo es de utilidad limitada en las zonas áridas. Aunque el aumento de la extensión del hábitat y la calidad en las áreas meso‐costeras puede funcionar, probablemente sea necesario emprender un manejo activo. Ya que la mayoría de la población de Australia se encuentra en áreas urbanas, los esfuerzos de resilvestreo deben incluir a las áreas urbanas para maximizar su efectividad. Por lo tanto, el resilvestreo no es sinónimo de la naturaleza y puede ocurrir en múltiples escalas. Los esfuerzos de resilvestreo deben reconocer los efectos que los humanos tienen sobre otras especies y deben beneficiar a la naturaleza y a las personas. El resilvestreo en Australia requiere del desarrollo de una visión compartida y de proyectos con prueba de concepto para demostrar sus beneficios. La reinvención de las actividades de conservación existentes como resilvestreo podría confundir y debilitar el éxito de los programas de resilvestreo, por lo que debería evitarse. Como en todos lados, el proceso de resilvestrar en Australia debería verse como una herramienta importante de conservación. 摘要: 野化正越来越多地被用于保护, 但它通常是环境特异的, 难以广泛应用。在澳大利亚, 野化项目旨在加强生态系统功能, 促进生态系统的自我维持。由于澳洲大陆缺乏大型本土食草动物, 因此考虑营养级联的野化项目主要关注顶级捕食者和小型哺乳动物的功能恢复。受到引入的中等体型捕食者带来的普遍影响, 野化中常常用到布设防捕食者围栏和在没有捕食者的岛屿上建立种群的方法。这使澳大利亚的野化有别于大多数国家和地区, 为全世界的野化项目提供了见解, 但也对在更大尺度的景观上进行功能恢复提出了挑战。在干旱地区, 被动野化的效果有限。尽管在湿度适中沿海地区, 扩大生境范围、提高生境质量可能有用, 但也需要进行积极的管理。由于澳大利亚大部分人口都生活在城市地区, 要实现效益最大化, 野化工作必须要包括城市地区。因此, 野化不等同于荒化, 且可以在多个尺度上进行。另外, 野化工作必须认识到人类对其它物种的影响, 并使自然和人类都能受益。澳大利亚的野化需要发展共同观念和概念验证项目来展现其效益。而若将现有的保护活动重新包装为野化, 可能会混淆和破坏野化项目的成功, 应注意避免。和其它地方一样, 澳大利亚也应该将野化作为一种重要的保护工具。【翻译: 胡怡思; 审校: 聂永刚】